2022
DOI: 10.1177/15569845221102179
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Term Outcomes of Totally Endoscopic Atrial Septal Defect Repair on Beating Heart in Small Children

Abstract: Objective: Manipulation in a narrow surgical field and risks of femoral arterial (FA) complications are difficulties when applying totally endoscopic surgery (TES) for congenital heart disease in small children. This study was conducted to investigate the feasibility of TES for atrial septal defect (ASD) repair in children weighing 13 to 20 kg. Methods: From July 2016 to July 2021, 14 patients with a mean age of 5.4 ± 2.2 years and mean weight of 15.57 ± 2.39 kg (range, 13 to 20 kg), underwent TES for ASD repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In ASD repair, a beating heart with pleural and pericardial cavities filled with CO 2 has many advantages, including (1) safety, (2) time savings and limited bleeding due to no touch on the ascending aorta, and (3) a more extensive surgical field. 1517 Through this study, we found that the absence of a transthoracic clamp allowed the SVC and related structures to be observed more clearly. In addition, the surgical steps on the SVC, including the SVC snaring, the first patch, and the second patch, could be done quickly with average times of 8.8 ± 3.4 min, 25.0 ± 9.6 min, and 25.9 ± 9.0 min, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 63%
“…In ASD repair, a beating heart with pleural and pericardial cavities filled with CO 2 has many advantages, including (1) safety, (2) time savings and limited bleeding due to no touch on the ascending aorta, and (3) a more extensive surgical field. 1517 Through this study, we found that the absence of a transthoracic clamp allowed the SVC and related structures to be observed more clearly. In addition, the surgical steps on the SVC, including the SVC snaring, the first patch, and the second patch, could be done quickly with average times of 8.8 ± 3.4 min, 25.0 ± 9.6 min, and 25.9 ± 9.0 min, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 63%
“…The rate of bilateral FA cannulation in this study was 26.8%, significantly lower than that of 71.4% in patients weighing <20 kg with the same CPB cannulation method. 8 We suggest that the immature vasoconstriction reflex may be the reason for this phenomenon.…”
Section: Discussionmentioning
confidence: 80%
“…10 TES in small patients with body weight <20 kg has more difficulties than the other group of patients, including (1) the risk of postoperative femoral arterial stenosis or obstruction and (2) the narrow surgical field making manipulation difficult. 8,12 However, TES for ASD repair without robotic assistance has not been widely applied, even in patients weighing ≥20 kg. Most published studies come from China, with a procedure similar to the traditional approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations